Prevalence, Antimicrobial Resistance, and Associated Factors of Streptococcus pneumoniae Colonization Rate among Old-Age Patients with Respiratory Tract Infection Attending Sheik Hassan Yebere Referral and Karamara General Hospitals, Jigjiga, Ethiopia - Surafel Mekuria; Ayichew Seyoum; Zerihun Ataro; Tigist Abebe; Kedir Urgessa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Streptococcus pneumoniae is part of the normal flora of the upper respiratory tract of humans. Colonization of the upper respiratory tract (carriage of pneumococcus) by S. pneumoniae is considered a prerequisite for pneumococcal infection. It is the major cause of respiratory tract infection and frequent cause of physician visits, hospitalization, and death among old-aged patients because of their low immunity status. However, data on S. pneumoniae among old-aged patients in eastern Ethiopia are limited. This study was undertaken to determine the prevalence, antimicrobial resistance, and associated factor of S. pneumoniae colonization among old-aged patients. Method. A health facility-based cross-sectional study was conducted from 1 March to 15 April 2020, at Sheik Hassan Yebere Referral and Karamara General Hospitals, Jigjiga, eastern Ethiopia. A total of 188 individuals greater than or equal to 60 years suspected of both upper and lower respiratory tract infections were included. Sociodemographic, behavioral, living conditions, and clinical data were collected by trained data collectors. Sputum samples were collected and examined for S. pneumoniae using the culture and biochemical tests as per the standard procedures. The Kirby–Bauer disk diffusion method was used for antimicrobial susceptibility testing. The data were entered on Epi-data version 3.1, and frequencies, crude odds ratio, and adjusted odds ratio were analyzed using SPSS version 20. Results. The prevalence of S. pneumoniae colonization rate among old-aged patients was 13.8% (26/188) (95% CI: 9.6–19.1). Smoking (AOR = 3.3; 95% CI: 1.3–8.3), upper airway problems (AOR = 4.1; 95% CI: 1.1–15), and asthma disease (AOR = 3.1; 95% CI: 1.1–8.9) were the factors associated with S. pneumoniae colonization. The isolated organisms showed high antimicrobial resistance to trimethoprim-sulphamethoxazole (n = 12, 46.2%), tetracycline (n = 11, 42.3%), and ampicillin (n = 9, 34.6%). Conclusion. This study showed that high prevalence of S. pneumoniae and antimicrobial resistance for trimethoprim-sulphamethoxazole, tetracycline, and ampicillin when compared to similar studies. Cigarette smoking, having upper airway problem, and asthma disease were factors associated with S. pneumoniae colonization. The provision of pneumococci conjugate vaccination and avoiding smoking are highly recommended for old aged in the community.